2004
DOI: 10.1074/jbc.m400813200
|View full text |Cite
|
Sign up to set email alerts
|

Calorimetric Studies on the Tight Binding Metal Interactions of Escherichia coli Manganese Superoxide Dismutase

Abstract: Escherichia coli apomanganese superoxide dismutase, prepared by removing the native metal ion under denaturing conditions, exhibits thermally triggered metal uptake behavior previously observed for thermophilic and hyperthermophilic superoxide dismutases but over a lower temperature range. Superoxide dismutases (SODs) 1 (E.C. 1.15.1.1) are important antioxidant metalloenzymes protecting cells against oxidative stress arising from reactive oxygen species (1-4). SODs are ubiquitous, and multiple forms often exis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
75
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(85 citation statements)
references
References 30 publications
9
75
0
1
Order By: Relevance
“…For example, when manganese binds to manganese superoxide dismutase of E. coli, the protein structure is stabilized as evidenced by the increased T m of manganese-bound proteins in thermo-unfolding experiments (apo-superoxide dismutase, T m ϭ 52.5°C; manganese superoxide dismutase, T m ϭ 68.6°C) (44). Likewise, manganese-bound prion protein resists higher concentrations of protease K, which also indicates the protein structure is stabilized by manganese (apo-prion, protease K ϭ 2 g/ml; manganese prion, protease K Ͼ25 g/ ml) (43).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, when manganese binds to manganese superoxide dismutase of E. coli, the protein structure is stabilized as evidenced by the increased T m of manganese-bound proteins in thermo-unfolding experiments (apo-superoxide dismutase, T m ϭ 52.5°C; manganese superoxide dismutase, T m ϭ 68.6°C) (44). Likewise, manganese-bound prion protein resists higher concentrations of protease K, which also indicates the protein structure is stabilized by manganese (apo-prion, protease K ϭ 2 g/ml; manganese prion, protease K Ͼ25 g/ ml) (43).…”
Section: Discussionmentioning
confidence: 99%
“…To acquire environmental manganese, the binding affinity of most manganese-binding proteins must be high (e.g. E. coli manganese superoxide dismutase, K D ϭ 3.12 nM) (44). Thus, the high affinity of Fbp68 for manganese would help overcome the low concentration of manganese both in vivo and in the environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Saccharomyces cerevisiae, conditions of mitochondrial iron overload, or manganese deficiency, result in the mismetallation with iron of the MnSOD homologue, SOD2 (48). Inappropriate iron binding to MnSOD inactivates the protein because of altered redox potential (48)(49)(50)(51)(52)(53). In this mouse model, however, there was no demonstrable misincorporation of iron into SOD2, even in iron-fed wild type mice that accumulate mitochondrial iron (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this protein is less stable than the human native enzyme. For the latter, differential scanning calorimetry 22 showed the first inactivation step at 68°C, followed by a main unfolding transition at about 88°C. Metal analysis, performed by atomic absorption spectroscopy, revealed that about two thirds of the metal binding sites are occupied by manganese ions.…”
Section: Sequence Analysis Of Rmnsodmentioning
confidence: 99%